ANALISIS KEUNTUNGAN USAHATANI PEPAYA CALIFORNIA (Carica papaya L.) DIDESA BATI-BATI KECAMATAN BATI-BATI KABUPATEN TANAH PROVINSI KALIMANTAN SELATAN - Zuraida; Yayuk Minta Wahyuningsih; Wasdiyanta (Fakultas Pertanian UVAYA Banjarmasin, 2024)
This research is entitled analysis of the profits of California papaya farming in Bati-Bati Village, Bati-bati District, Tanah Laut Regency, South Kalimantan Province from February to April 2024, with technical and financial objectives, a method of drawing a sample of sample farmers using the case study method with total cost results spent amounting to Rp. 49,960,416, the total income of farmers is Rp. 189,000,000,- / 3 months so that the total profit of papaya farmers for 3 month is Rp. 139,039,584,-